(untitled) (Jurnal Simki Economic, 2023)
The social media platform that is currently popular is Instagram, with a user base of 109.3 million people as of April 2023. This number has continued to increase by 3.45% compared to March, which had 105.68 million users. With the large number of Instagram users, there has been a rise in online stores that create accounts and utilize various features on Instagram for trading purposes. As more online stores open accounts on Instagram, many users become more consumptive upon seeing posts on their Instagram timeline. Therefore, the author intends to analyze the influence of Instagram on users’ online shopping behavior. The research was conducted by distributing questionnaires to respondents through the social media platform Twitter and analyzing the questionnaire data using SEM-GesCA. There were 96 respondents who completed the questionnaire, with 52% of them being male. The results obtained from this study indicate that the social media platform Instagram has a negative influence on users’ online shopping behavior.